STUDI FENOMENOLOGI ATAS IMPLEMENTASI AKUNTANSI BERBASIS AKRUAL PADA BADAN LAYANAN UMUM DAERAH RSUD DR. SAIFUL ANWAR MALANG - Rachmawati Rachmawati; Ali Djamhuri; Wuryan Andayani (Jurnal Akuntansi Aktual, 2018)
This research is aimed to obtain deep understanding about the meaning of accrual based accounting implementation based on financial management experience in Saiful Anwar hospital. Through Husserl's phenomenology, the implementation of accrual-based accounting is interpreted as "making us uncertain" and "complicated" which ultimately leads to the awareness that the presence of accrual-based accounting is interpreted as one of the "needs" to control all operational activity in Saiful Anwar hospital. In the facts, the application of accrual-based accounting in RSSA has not been fully applicable, especially in financial filing report based on SAK. It is because the obstacle coming from the internal itself. One of the obstacles faced in implementing these standards is the accounting system that has not been integrated with all units in RSSA so as to affect the accuracy and speed of time in the preparation of the financial statements of RSSA due to the preparation of financial statements are still manually implemented.